Perspectives from science teacher educators on the potential contribution of Sámi traditional knowledge to sustainable development - Melis, Claudia; Kvivesen, Mona; Munkebye, Eli (Frontiers in Education, 2025)
IntroductionThis study investigates how Sámi traditional knowledge is integrated in science teacher education in Norway, and what teacher educators declare about its potential contribution to sustainable development.MethodsData was collected through an anonymous electronic survey and analyzed by means of both qualitative and quantitative methods. Thirty-nine respondents from 15 teacher education institutions in Norway participated in the study.ResultsAccording to the respondents, most science courses explicitly mentioned Sámi traditional knowledge. The most common Sámi topics taught in science in kindergarten education, were the seasons, preparing traditional food, constellations and reflecting about how traditional knowledge can contribute to sustainability. For primary school teacher education, the most common Sámi topics were the constellations, conflicts with building of windmills parks in traditional reindeer grazing areas, traditional use of plants and seasons. The self-declared level of knowledge on Sámi traditional knowledge was rather low and the majority of respondents expressed the intention to improve their competence by reading or attending courses. The thematic analysis of the answers to the question about how Sámi traditional knowledge could contribute to sustainable development, identified four main Sámi themes: traditional use of resources, view of nature, local knowledge versus Sámi traditional knowledge, and social sustainability. Our results confirmed that teaching Sámi traditional knowledge poses a significant challenge for science teacher educators, both as consequence of their perceived knowledge and the limited amount of time available for teaching. Some respondents found the subject not relevant for the students, whereas other were challenged by its sensitivity or by the availability of culture bearers. The contrast between traditional knowledge and western science as different views of knowledge was also mentioned.DiscussionBased on teacher educators’ perspectives, we propose that adopting a Two-Eyed Seeing approach in science teaching could promote critical thinking, by enabling a reflection on our resource utilization and on our human-nature relationship. Some of the challenges associated with lack of time and knowledge could be addressed by promoting further education for science teacher educators, building a network of knowledge bearer that could be invited in the teacher courses, or reevaluating the courses content to make place for Sámi themes. This would also promote decolonization and inclusion of the Sámi people, thus contributing to several aspects of sustainability.